2023
DOI: 10.1109/jflex.2023.3234894
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated Flexible Photonic Crystal Slabs for Refractive Index and Biomolecular Sensing

Abstract: Using the optical transduction properties of onedimensional photonic crystal slabs is a promising approach for label-free biosensing in the field of flexible and wearable biosensing. In this work we demonstrate the fabrication of flexible photonic crystal slabs (f-PCS) via an exfoliation method from rigid photonic crystal slabs. We investigate the processing effect on the optical properties and show that the optical resonances are maintained, but affected. The quality factor changes from 50 to 31 for the TE mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…28 The exfoliated flexible photonic crystal slabs were able to detect the cat IgG of 38 to 56 μg mL −1 , and APTES, PDITC and DMF sequentially used to modify the TiO 2 surface, and protein A was used to immobilize the capture antibody. 29 Comparing the above biosensors, we concluded that the biosensing capability of the modification using TESBA on the TiO 2 surface was better than those of other methods.…”
Section: Resultsmentioning
confidence: 88%
“…28 The exfoliated flexible photonic crystal slabs were able to detect the cat IgG of 38 to 56 μg mL −1 , and APTES, PDITC and DMF sequentially used to modify the TiO 2 surface, and protein A was used to immobilize the capture antibody. 29 Comparing the above biosensors, we concluded that the biosensing capability of the modification using TESBA on the TiO 2 surface was better than those of other methods.…”
Section: Resultsmentioning
confidence: 88%
“…To functionalize the surface of the photonic crystal, silanes (3-Aminopropyl)triethoxysilane (APTES) (440140, Sigma-Aldrich, USA), dry methanol (322415, Sigma-Aldrich, Saint Louis, MO, USA), Dulbecco’s Phosphate Buffered Saline (DPBS) (D8537, Sigma-Aldrich, USA) and a cross-linking solution were used. The cross-linking solution was fabricated with 200 mg PDITC (258555, Sigma-Aldrich, USA) dissolved in 1 mL pyridine (270970, Sigma-Aldrich, USA) and 9 mL N,N-dimethylformamid (DMF) (227056, Sigma-Aldrich, USA) [ 16 ]. BSA-biotin (A8549, Sigma-Aldrich, USA) was immobilized onto the photonic crystal and BSA (05470, Sigma-Aldrich, USA) was used for passivation at the end of the functionalization process.…”
Section: Methodsmentioning
confidence: 99%
“…The optical detection methods surface plasmon resonance (SPR) and total internal reflection ellipsometry (TIRE) are used in highly sensitive, label-free biosensors, but are high-cost and require bulky equipment [ 13 , 15 ]. Guided mode resonance (GMR) sensors, also known as photonic crystal slab sensors, are easier to miniaturize into label-free biosensors [ 8 , 16 , 17 , 18 , 19 , 20 , 21 ]. They can be functionalized [ 22 ] with antibodies or aptamers to detect biomarkers such as proteins or small molecules [ 17 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We fabricate stable photonic crystal slabs (sPCS) based on a nanoimprint lithography process [17,35]. The process is depicted in Fig.…”
Section: Fabrication Of Stable Photonic Crystal Slabs (Spcs)mentioning
confidence: 99%
“…Flexible photonic crystals have seen an uptake in research activity within recent years [6,7]. They have been studied for various applications, such as flexible optical elements [8][9][10][11][12][13], as anticounterfeiting marks in information security [14,15], as an embedded sensor for food security [16], for label-free biosensing [17], and for strain gauging [18][19][20][21][22][23]. The latter is based on the mechanochromism effect, which is a change of resonance wavelength induced by external mechanical stress [24].…”
Section: Introductionmentioning
confidence: 99%